Designing An Android-Based Advergame Using Unity 3d And Firebase - Muhammad Rasyiddin (Journal of Social Research, 2025)
The high growth value of the culinary industry compared to other industries has caused the number of competitors owned by Kedai UKM to increase. So that to stay competitive, Kedai UKM uses an advertising strategy in the form of social media. However, because it was deemed ineffective, Kedai UKM needed a new innovation in promoting UKM shops. One form of innovation in the advertising world is to use a video game. Advergame is a form of advertising that is currently booming used to advertise a product or brand where the product or brand is inserted into a video game (In-Advertising Game) or turning the product or brand into a video game (Pure Advertising Game). The results obtained from this study are in the form of an advergame prototype for the Kedai UKM restaurant, where the advertised brand and product will be inserted into a video game that is built into an application prototype with the Android platform. The application is built using the Rapid Application Development method using Unity3D software. To see whether the application prototype has a positive response from visitors who come, the application will be tested using a due diligence. If the average score exceeds 3 out of 5, the application and research will be considered feasible and successful.